Volunteer Performance Model Through Leadership Motivation Training Loyalty: Model Kinerja Relawan Melalui Pelatihan Motivasi Kepemimpinan dan Loyalitas - Rahmatulloh Gustiamtomo; Vera Firdaus (Indonesian Journal of Public Policy Review, 2026)
General Background Volunteer performance is a critical factor in achieving organizational goals, particularly in non-profit institutions relying on voluntary participation. Specific Background In humanitarian organizations, leadership style, motivation, and training are considered key determinants influencing volunteer outcomes. Knowledge Gap Previous studies mainly focus on commercial institutions, leaving limited exploration within non-profit volunteer contexts and the mediating role of loyalty. Aims This study aims to analyze the relationships between servant leadership, motivation, and training on volunteer performance, with loyalty as an intervening variable. Results The findings reveal that servant leadership, motivation, training, and loyalty each have a positive and significant effect on volunteer performance. Additionally, servant leadership, motivation, and training significantly influence volunteer loyalty, and loyalty successfully mediates these relationships. Novelty This research provides empirical evidence within a non-commercial humanitarian organization context, highlighting loyalty as a mediating mechanism. Implications The results suggest that strengthening leadership approach, motivation, and structured training can support volunteer loyalty and performance improvement in non-profit organizations. Keywords: Volunteer Performance, Volunteer Loyalty, Servant Leadership, Motivation, Training Key Findings Highlights Leadership, internal drive, and structured development shape volunteer outcomes Commitment acts as a linking mechanism between organizational practices and results Empirical evidence derived from humanitarian organizational context